Assessing Virtual Reality Fire Extinguisher Training Effectiveness: A Quantitative Empirical Study - Kamal, Rida; Hossain, A. K. M. Ishtyak; Heilala, Janne; Kantola, Jussi (United States, 2026)
This study conducts a quantitative assessment based on empirical evidence to measure the effectiveness of virtual reality-based fire extinguisher training. The data were collected from 71 participants who first underwent virtual reality (VR) fire extinguisher training and then practical fire extinguisher training with a gap of one week between these sessions. After finishing the practical training, participants filled out a structured quantitative questionnaire evaluating five key aspects: Knowledge Acquisition, Knowledge Retention, Realism, Usability, and Engagement. To assess the effectiveness and identify the stronger predictor of the effectiveness, a quantitative analysis was conducted encompassing descriptive statistics, t-tests, and regression analysis. The findings from this research reveal that Engagement and Usability were ranked highest in terms of the effectiveness of VR training. Participants felt that for VR training Engagement and Usability enhanced their overall experience. Furthermore, Engagement and Usability had the strongest impact on the effectiveness of the overall training. Respondents also reflected on the insufficiency of the VR environment in relation to realism, emphasizing the need for advancements in this area. These results imply that VR is an effective, engaging, and usable tool for safety training, but that refinements in interactive fidelity are needed in order to boost learning outcomes. Future research may investigate realism enhancements and knowledge retention strategies to further optimize VR-based safety training programs.
Human Factors, Business Management and Society: Proceedings of the 16th International Conference on Applied Human Factors and Ergonomics and the Affiliated Conferences, Orlando, Florida, USA 26-30 July 2025